Innovative curricular approach in public health from a perspective of the right to health, critical focus of social determinants and health citizenship. Cali, Colombia. 2010-2018 - Arrivillaga, Marcela (2019)
Introduction: The Medicine Program of the Pontificia Universidad Javeriana Cali in Colombia began in 2010, including in its curriculum educational environments that aim to train medical students with a comprehensive vision of health and life. Objective: To document the curricular innovation in public health implemented in the program between 2010 and 2018 that has been oriented to transform the training approach in medical education. Materials and methods: Qualitative case study with documentary review. We used the “wheel method” to present the principles that guided the innovative approach. Results: We found four principles: ethical, political, theoretical and pedagogical. This implies the unrestricted defense of the right to health and the education in health citizenship from a critical focus of social determinants. It seeks the appropriation of social and humanistic competences through practices in vulnerable communities in Cali. Conclusions: This approach opens opportunities to reformulate the medical education, and expands training to build competencies that respond to the “health-disease-care” process.